Radioimmunoassay for acetylcholin - Bao Zhong-qi; Ling Shi-gan; Liu Fang-mei; Wang Guang-yuan; Li Ling (Acta Pharmacologica Sinica, 2016)
The titre of the anti-ACh serum was 1:1000 which gave about 40% binding. Millipore membrane filter was utilized to separate the “bound” antibody from "free” [3H] ACh. The detection limit of ACh was 2.5 pmol. The accuracy, precision and reproducibility of this method indicate that it would be useful for ACh determinations in tissues. The ACh contents of the whole brain of normal and physostigmine-injected (ip) mice were determined. Rats were killed by 1) decapitation, 2) decapitation plus rapid freezing by liquid N2, and 3) microwave irradiation. The results of microwave irradiation group were higher than those of the other 2 groups.